2019
DOI: 10.1097/sla.0000000000003519
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal or Extracorporeal Ileocolic Anastomosis After Laparoscopic Right Colectomy

Abstract: Objectives: The aim of the study was to determine whether there are clinically relevant differences in outcomes between laparoscopic right colectomy (LRC) with intracorporeal ileocolic anastomosis (IIA) and LRC with extracorporeal IA (EIA). Background: IIA and EIA are 2 well-established techniques for restoration of bowel continuity after LRC. There are no high-quality studies demonstrating the superiority of one anastomotic technique over the other. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
130
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(147 citation statements)
references
References 39 publications
14
130
3
Order By: Relevance
“…As the third randomized trial on this topic, Bollo et al . seem to be in line with the results of other studies, reinforcing the advantages of IA.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…As the third randomized trial on this topic, Bollo et al . seem to be in line with the results of other studies, reinforcing the advantages of IA.…”
supporting
confidence: 76%
“…Postoperative outcomes favoured IA for both bowel function recovery and pain, but with no differences in time to first oral intake, severity of complications, median length of hospital stay, 30‐day morbidity rate, incisional hernia rate or median number of lymph nodes. Although not statistically significant, the anastomotic leak rate in IA was higher than in EA (8·6 versus 2·9 per cent).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…On the one hand, a recent meta-analysis including 3755 patients found that in IA, time to rst atus, time to defecation, time to liquid diet, hospital length of stay, postoperative infections and overall complications were estimated to be lower [22] . On the other hand, Kang Hong Lee et.al [23] found that the number of retrieved lymph nodes, the overall survival and the disease-free survival at three years were not signi cantly different between IA and EA. The resection and anastomosis need not be performed extracorporeally for IA and therefore a smaller portion of the intestine is required to be freed laparoscopically.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, the surgeon is able to perform a less invasive surgery on the basis of radical oncological outcomes. Since the development of intracorporeal anastomosis [8] , complete laparoscopic extended hemicolectomy with preserving the ileocecal junction may be an optional procedure for right-transverse colon cancer. Therefore, we try to apply this procedure in the laparoscopic treatment for right-transverse colon cancer and explore its safety and feasibility.…”
Section: Introductionmentioning
confidence: 99%